Carbon-coated foil as well as pole piece and battery applying same

By setting a carbon layer on the surface of the carbon coated foil and introducing a self-healing hydrogel, the problem of insufficient toughness of the carbon coated foil is solved, the self-healing effect of the foil is achieved, and its toughness and crack resistance are improved.

CN119581571AInactive Publication Date: 2025-03-07YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510127652.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The toughness of existing carbon coated foils is poor, resulting in easy breakage when slicing, rewinding or coating active substances.

Method used

A carbon layer is provided on the surface of the foil and a self-healing hydrogel is introduced into the carbon layer. The self-healing hydrogel is re-crosslinked through reversible reactions of non-covalent bonds or covalent bonds to achieve self-healing, thereby improving the toughness of the foil.

Benefits of technology

Through the application of self-healing hydrogel, the toughness and crack resistance of carbon coated foils are improved, the risk of fracture is reduced, and good fatigue resistance is given.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a carbon-coated foil, and a pole piece and a battery using the same. The carbon-coated foil material comprises a foil material and a carbon layer arranged on at least one surface of the foil material, and the carbon layer contains self-repairing hydrogel. The self-repairing hydrogel is introduced into the carbon layer, the self-repairing hydrogel contains a large number of non-covalent bonds or covalent bonds, when the carbon-coated foil is stimulated by the outside, the self-repairing hydrogel can be crosslinked again through the reversible reaction of the non-covalent bonds or covalent bonds in the self-repairing hydrogel, the self-repairing process is completed, and self-healing is achieved; when the carbon-coated foil is damaged under stress stretching, the self-repairing hydrogel in the carbon layer is subjected to reversible reaction and re-crosslinking through non-covalent bonds or covalent bonds to repair the damaged part of the foil on the microscopic scale, so that the toughness of the carbon-coated aluminum foil is improved, the carbon-coated foil is endowed with good crack resistance and fatigue resistance, and the service life of the carbon-coated foil is prolonged. And the risk that the carbon-coated foil is easy to break during slitting, rewinding or active substance coating is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a carbon-coated foil, a pole piece and a battery using the same. Background Art

[0002] Lithium-ion batteries are batteries that rely on the movement of lithium ions between the positive and negative electrodes to achieve charging and discharging. Due to their advantages such as high energy density, high operating voltage, no memory effect, no pollution, and cyclability, they have been widely used in many fields such as consumer electronics, transportation, power tools, and energy storage.

[0003] Lithium-ion batteries mainly include positive electrode sheets, negative electrode sheets, separators and electrolytes. In lithium-ion batteries, foil is usually used as a carrier of active substances. In order to improve the performance of the foil, a conductive slurry containing a conductive agent is usually coated on the surface of the foil to obtain a carbon-coated foil. This carbon-coated foil can increase wettability and adhesion, reduce polarization internal resistance, and improve the consistency of lithium-ion batteries. However, the toughness of the carbon-coated foil is poor, which makes the carbon-coated foil easy to break when slitting, rewinding or coating the active substance. Summary of the invention

[0004] In order to solve the problem that the existing carbon-coated foil has poor toughness, which causes the foil to break easily when slitting, rewinding or coating active materials, the present invention provides a carbon-coated foil, a pole piece and a battery using the same.

[0005] According to a first aspect of the present invention, a carbon-coated foil is provided. The carbon-coated foil comprises a foil and a carbon layer disposed on at least one surface of the foil, wherein the carbon layer contains a self-healing hydrogel.

[0006] Hydrogel is a special material with a three-dimensional network structure formed by physical or chemical crosslinking of high molecular weight polymers.

[0007] Self-healing hydrogels can be divided into two categories according to the repair mechanism: the first category is the external self-healing hydrogel introduced into the hydrogel by introducing materials such as microcapsules; the second category is the intrinsic self-healing hydrogel through the interaction between the molecular chains in the hydrogel. The intrinsic self-healing hydrogel essentially introduces the dynamic reversible properties of supramolecular chemistry into polymer materials, completing the self-healing of the material in the process of re-identification and construction of covalent or non-covalent bonds. Therefore, the intrinsic repair of self-healing hydrogels is divided into two types: physical dynamic self-healing through non-covalent cross-linking and chemical dynamic self-healing through reversible dynamic covalent cross-linking.

[0008] In the carbon-coated foil provided by the present invention, a self-healing hydrogel is introduced into the carbon layer provided on the surface of the foil. Since the self-healing hydrogel contains a large number of non-covalent bonds (such as hydrogen bonds, hydrophobic forces, crystals, etc.) or covalent bonds (such as acylhydrazone bonds, imine bonds, disulfide bonds, Diels-Alder reversible covalent bonds, etc.), when the carbon-coated foil is subjected to external stimulation, the self-healing hydrogel can be re-cross-linked through the reversible reaction of the non-covalent bonds or covalent bonds therein to complete the self-healing process, thereby achieving self-healing. Therefore, when the carbon-coated foil is damaged under stress stretching, the self-healing hydrogel in the carbon layer is reversibly cross-linked through the non-covalent bonds or covalent bonds to repair the damaged parts of the foil at the microscopic level. The toughness of the carbon-coated aluminum foil is improved through the above-mentioned action, and the carbon-coated foil is given good crack resistance and fatigue resistance, thereby reducing the risk of the carbon-coated foil being easily broken during slitting, rewinding or coating with active substances.

[0009] Preferably, the self-healing hydrogel comprises a cellulose-based hydrogel.

[0010] Preferably, the cellulose-based hydrogel includes at least one of sodium carboxymethylcellulose hydrogel, sodium hydroxyethylcellulose hydrogel, sodium hydroxypropylmethylcellulose hydrogel, cellulose ether hydrogel, and nanocellulose hydrogel.

[0011] Preferably, the cellulose-based hydrogel includes at least one of sodium carboxymethylcellulose hydrogel, sodium hydroxyethylcellulose hydrogel and sodium hydroxypropylmethylcellulose hydrogel.

[0012] Preferably, the cellulose-based hydrogel further comprises microcapsules, wherein the microcapsules comprise a repair material and a shell encapsulating the repair material.

[0013] Preferably, the repair material comprises a cellulose derivative and a cellulase.

[0014] By introducing microcapsules formed by wrapping the repair material cellulose derivative and cellulase with a shell into the cellulose-based hydrogel, the activity of the cellulase can be guaranteed. The cellulose-based hydrogel containing the above-mentioned microcapsules is applied to the carbon layer of the carbon-coated foil. When the carbon-coated foil is damaged under stress stretching, the microcapsules will rupture and release the repair agent cellulose derivative and cellulase. The released cellulase can catalyze the repair reaction of the cellulose-based hydrogel, causing the cellulose derivative to re-cross-link. The damaged parts of the carbon-coated foil can be blocked by the re-cross-linked cellulose-based hydrogel, thereby enabling the damaged carbon-coated foil to self-heal, further improving the flexibility of the carbon-coated foil.

[0015] Preferably, the cellulose derivative includes at least one of sodium carboxymethyl cellulose, sodium hydroxyethyl cellulose and sodium hydroxypropyl methyl cellulose.

[0016] Cellulase can degrade naturally occurring cellulose, but cannot degrade artificially synthesized high-molecular-weight cellulose derivatives. By introducing the above-mentioned cellulose derivatives into the repair material of the microcapsules contained in the cellulose-based hydrogel, these cellulose derivatives are all artificially synthesized high-molecular-weight compounds. The cellulase in the microcapsules cannot capture and recognize the carboxylmethyl, hydroxyethyl, hydroxypropyl and other groups in these cellulose derivatives, and thus it is difficult to degrade these cellulose derivatives. Therefore, the repair material cellulose derivatives and cellulase contained in the microcapsules in the cellulose-based hydrogel can maintain good structural stability and synergistically play a repairing role on the damaged carbon-coated foil.

[0017] Preferably, the outer shell is formed by cross-linking glucose.

[0018] Glucose will be dehydrated and cross-linked to polymerize into a macromolecule under the hydrothermal reaction. Using glucose as a raw material to prepare the shell of the microcapsule is beneficial to maintaining good activity of the repair material in the microcapsule. When the carbon-coated foil is damaged, the repair material can better play a role in repairing the damaged carbon-coated foil, which is beneficial to improve the toughness of the carbon-coated foil.

[0019] Preferably, the sodium carboxymethyl cellulose hydrogel is prepared by the following steps: S1. mixing the first solvent with glucose to obtain a glucose solution; S2. mixing hydrogen peroxide with a cellulose derivative to prepare a suspension; S3. Add the repair material to the suspension and mix well to obtain a first mixed solution; S4. Mixing the glucose solution with the first mixed solution to obtain a second mixed solution; S5. Allow the second mixed solution to undergo a hydrothermal reaction to obtain a cellulose-based hydrogel, wherein the temperature of the hydrothermal reaction is 110-130°C.

[0020] This scheme uses cellulose derivatives as raw materials, and makes glucose undergo hydrothermal reaction at a temperature of 110~130℃ to dehydrate and undergo cross-linking to polymerize into a polymer to form an outer shell to coat the repair material to form microcapsules, thereby preparing a cellulose-based hydrogel containing microcapsules. The prepared cellulose-based hydrogel containing microcapsules is applied to the carbon layer of carbon-coated aluminum foil. When the carbon-coated foil is damaged, the non-covalent bonds (such as hydrogen bonds, hydrophobic forces) in the cellulose-based hydrogel and the repair agent released after the microcapsules are ruptured can repair the damaged carbon-coated foil, so that the damaged part of the carbon-coated foil can be self-healed, thereby improving the toughness of the carbon-coated foil, improving the crack resistance and tensile resistance of the carbon-coated foil, and reducing the risk of fracture of the carbon-coated foil.

[0021] Preferably, in S1, the mass ratio of the first solvent to glucose is 7-9:1-3.

[0022] Preferably, in S1, the first solvent is deionized water.

[0023] Preferably, in S2, the mass ratio of hydrogen peroxide to cellulose derivative is 3-7:0.5-2.

[0024] Preferably, in S2, the mass percentage of hydrogen peroxide is 0.5-2%.

[0025] In the preparation process of carboxymethyl cellulose-based hydrogel, by introducing hydrogen peroxide with a concentration of 0.5-2% into the cellulose derivative, other impurities in the cellulose derivative can be removed, the purity of the cellulose derivative can be improved, the purity of the obtained cellulose-based hydrogel can be improved, and the mechanical properties of the carbon-coated foil can be further improved. In addition, hydrogen peroxide at this concentration takes many days at room temperature to decompose the cellulose derivative into low molecular materials such as sodium ions, carboxymethyl / hydroxyethyl / hydroxypropyl and cellulose, while the process of preparing the suspension using hydrogen peroxide and cellulose derivative in S2 only involves simple mixing at room temperature, and the cellulose derivative will not decompose. In the subsequent hydrothermal reaction, hydrogen peroxide will decompose into water and oxygen at a temperature of 110-130°C, and will not interfere with the various components used in the preparation process of the cellulose-based hydrogel.

[0026] Preferably, the mass fraction of the self-healing hydrogel in the carbon layer is 0.1-10%.

[0027] Controlling the content of self-healing hydrogel in the carbon layer within the above range can not only make the damaged part of the carbon-coated foil self-heal and improve the toughness of the carbon-coated foil, but also will not affect the performance of the carbon-coated foil. In addition, the toughness of the carbon-coated foil increases with the increase of the content of self-healing hydrogel in the carbon layer, but after the content of self-healing hydrogel in the carbon layer exceeds 10%, the toughness of the carbon-coated foil will gradually stabilize, while the electrical performance will decrease.

[0028] Preferably, the carbon-coated foil is prepared by the following steps: S1. mixing the second solvent with the binder to obtain a glue solution; S2. Add a conductive agent to the glue solution and mix well to obtain a first slurry; S3. Adding a third solvent and a self-healing hydrogel to the first slurry and mixing them evenly to obtain a conductive slurry; S4. Applying a conductive paste on at least one surface of the foil to form a carbon layer to obtain a carbon-coated foil.

[0029] Preferably, calculated by mass ratio, the binder: conductive agent: self-healing hydrogel = 5~15: 10~20: 0.05~2.5.

[0030] Preferably, the second solvent is deionized water.

[0031] Preferably, the third solvent is deionized water.

[0032] Preferably, the binder includes at least one of acrylate, polyacrylic acid, modified polyacrylic acid, and waterborne polyurethane.

[0033] Preferably, the binder is polyacrylic acid with a solid content of 15-30% and a viscosity of 200-1500 mPas.

[0034] According to a second aspect of the present invention, a pole piece is provided, the pole piece comprising the above-mentioned carbon-coated foil.

[0035] According to a third aspect of the present invention, a battery is provided, comprising the above-mentioned electrode sheet.

[0036] Applying the carbon-coated foil provided by the present invention to pole pieces can improve the flexibility of the pole pieces, reduce the risk of pole piece breakage, and thus improve the safety performance of the battery. DETAILED DESCRIPTION

[0037] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0038] Example 1 A carbon-coated aluminum foil, comprising an aluminum foil and a carbon layer disposed on two surfaces of the aluminum foil, wherein the carbon layer contains a carboxymethyl cellulose hydrogel, the carboxymethyl cellulose hydrogel comprises a microcapsule, the microcapsule comprises a repair material and a shell covering the repair material, the repair material comprises cellulase and sodium carboxymethyl cellulose, wherein the mass ratio of the cellulase to the sodium carboxymethyl cellulose is 1:1; The carbon-coated aluminum foil provided in this embodiment is prepared by the following steps: (1) Preparation of sodium carboxymethyl cellulose hydrogel powder S1. Take 8 parts by weight of deionized water and 2 parts by weight of glucose and stir for 30 min until the solution is clear and transparent to obtain a glucose solution; S2. Take 4 parts by weight of hydrogen peroxide and 1 part by weight of sodium carboxymethyl cellulose and mix them for 5 min so that the solution is in a suspension state to obtain a suspension; S3. according to the mass ratio of cellulase to suspension being 1:6, cellulase (purchased from DuPont China Group Co., Ltd., model number Accellerase 2000) was added to the above suspension and mixed and stirred for 30 minutes to obtain a first mixed solution; S4. The glucose solution was mixed with the first mixed solution, and 5 parts by weight of deionized water was added thereto, and the mixture was stirred for 1 h to obtain a second mixed solution; S5. The second mixed liquid was transferred to a Teflon hydrothermal reactor and subjected to a hydrothermal reaction at 120°C for 12 hours. After complete cooling, the upper clear solution was taken out with a dropper and the lower viscous liquid was retained. The viscous liquid obtained after the reaction was put into a centrifuge tube and centrifuged at 3000 r / min for 30 min. The lower layer of colloid was taken out and placed in a culture dish. The tube was baked in a vacuum drying oven at 60°C for 24 hours to obtain sodium carboxymethyl cellulose hydrogel powder.

[0039] (2) Preparation of carbon-coated aluminum foil S1. Mixing deionized water with aqueous polyacrylic acid (aqueous PAA, viscosity of 4000-8000 mPa·s) to reduce the solid content of the binder to obtain a glue solution with a solid content of 500 mPa·s; S2. Add 50% of the total mass of the first conductive agent carbon powder and 50% of the total mass of the second conductive agent graphite powder to the above-mentioned glue, and disperse them at a high speed of 2000~2600 rpm / min in a 200 L double star stirring tank for 30 min, then add the remaining first conductive agent carbon powder and second conductive agent graphite powder, and disperse them at a high speed of 2000~2600rpm / min in a 200 L double star stirring tank for 60 min to obtain a first slurry; S3. Add an appropriate amount of deionized water to the first slurry and disperse it at a high speed of 2000-2600 rpm / min in a 200 L double star stirring tank for 30 min to reduce the viscosity, add a pH adjuster thereto, adjust the pH of the system to 5-7, then add the above-mentioned sodium carboxymethyl cellulose hydrogel powder thereto, disperse it at a high speed of 100-500 rpm / min in a 200 L double star stirring tank for 120 min, then add a wetting agent thereto, stir it at a low speed of 10-15 rpm / min in a 200 L double star stirring tank for 30-45 min, discharge the material, and homogenize the slurry twice in a homogenizer at a pressure of 300 bar to obtain a conductive slurry; S4. The conductive paste is coated on both surfaces of the aluminum foil to form a carbon layer to obtain a carbon-coated aluminum foil; Among them, the mass ratio of the binder, the first conductive agent carbon powder, the second conductive agent graphite powder, and the sodium carboxymethyl cellulose hydrogel powder used to prepare the carbon-coated aluminum foil is 6:7:3:1.

[0040] Example 2 This embodiment provides a carbon-coated aluminum foil. Compared with the embodiment 1, the difference in structure is: (1) in the preparation step S2 of the hydrogel powder, an equal amount of cellulose ether is used to replace sodium carboxymethyl cellulose; (2) in the preparation step S3 of the carbon-coated aluminum foil, an equal amount of cellulose ether hydrogel powder is used to replace sodium carboxymethyl cellulose hydrogel powder. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0041] Example 3 This embodiment provides a carbon-coated aluminum foil. Compared with the embodiment 1, the difference in structure is: (1) in the preparation step S2 of the hydrogel powder, an equal amount of nanocellulose is used to replace sodium carboxymethylcellulose; (2) in the preparation step S3 of the carbon-coated aluminum foil, an equal amount of nanocellulose hydrogel powder is used to replace sodium carboxymethylcellulose hydrogel powder. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0042] Example 4 This embodiment provides a carbon-coated aluminum foil. Compared with the embodiment 1, the difference in structure is that in the step S3 of preparing the carbon-coated aluminum foil, an equal amount of carboxymethyl xylan hydrogel powder (purchased from DuPont China Group Co., Ltd., model number Walocel CRT 1000P) is used to replace the sodium carboxymethyl cellulose hydrogel powder. Except for the above difference, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0043] Example 5 This embodiment provides a carbon-coated aluminum foil. Compared with the embodiment 1, the difference in structure is that in the step S3 of preparing the carbon-coated aluminum foil, an equal amount of carboxymethyl guar gum hydrogel powder is used to replace the sodium carboxymethyl cellulose hydrogel powder. Except for the above difference, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0044] Example 6 This embodiment provides a carbon-coated aluminum foil. Compared with Embodiment 1, the differences in structure are: (1) the shell of the microcapsule in the sodium carboxymethyl cellulose hydrogel is made of polyvinyl alcohol; (2) in the preparation step S1 of the sodium carboxymethyl cellulose hydrogel powder, an equal amount of polyvinyl alcohol is used to replace glucose.

[0045] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0046] Example 7 This embodiment provides a carbon-coated aluminum foil. Compared with Embodiment 1, the differences in structure are: (1) the shell of the microcapsule in the sodium carboxymethyl cellulose hydrogel is made of chitosan; (2) in the preparation step S1 of the sodium carboxymethyl cellulose hydrogel powder, an equal amount of chitosan is used to replace glucose.

[0047] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0048] Example 8 This embodiment provides a carbon-coated aluminum foil. Compared with the embodiment 1, the difference in structure is: (1) the repair material in the microcapsules in the sodium carboxymethyl cellulose hydrogel is methyl dimethacrylate; (2) in the preparation step S3 of the sodium carboxymethyl cellulose hydrogel powder, an equal amount of methyl dimethacrylate is used to replace cellulase. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0049] Example 9 This embodiment provides a carbon-coated aluminum foil. Compared with the embodiment 1, the difference in structure is: (1) the repair material in the microcapsules in the sodium carboxymethyl cellulose hydrogel is colloidal gold; (2) in the preparation step S3 of the sodium carboxymethyl cellulose hydrogel powder, an equal amount of colloidal gold is used to replace cellulase. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0050] Example 10 This embodiment provides a carbon-coated aluminum foil. Compared with Embodiment 1, the differences in structure are: (1) the sodium carboxymethyl cellulose hydrogel does not contain microcapsules; (2) in the preparation step S3 of the carbon-coated foil, polyethylene glycol is added simultaneously with the addition of sodium carboxymethyl cellulose powder, wherein the mass ratio of the sodium carboxymethyl cellulose hydrogel powder to the polyethylene glycol is 0.01:0.05.

[0051] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.

[0052] Embodiment 11 This embodiment provides a carbon-coated aluminum foil. Compared with the embodiment 1, the difference in composition is that the mass ratio of the binder, the first conductive agent carbon powder, the second conductive agent graphite powder, and the sodium carboxymethyl cellulose hydrogel powder used to prepare the carbon-coated aluminum foil is 6:7:3:0.01. Except for the above differences, the materials, formula ratios, and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0053] Example 12 This embodiment provides a carbon-coated aluminum foil. Compared with the embodiment 1, the difference in composition is that the mass ratio of the binder, the first conductive agent carbon powder, the second conductive agent graphite powder, and the sodium carboxymethyl cellulose hydrogel powder used to prepare the carbon-coated aluminum foil is 6:7:3:0.5. Except for the above differences, the materials, formula ratios, and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0054] Embodiment 13 This embodiment provides a carbon-coated aluminum foil. Compared with the embodiment 1, the difference in composition is that the mass ratio of the binder, the first conductive agent carbon powder, the second conductive agent graphite powder, and the sodium carboxymethyl cellulose hydrogel powder used to prepare the carbon-coated aluminum foil is 6:7:3:3. Except for the above differences, the materials, formula ratios, and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0055] Comparative Example 1 This comparative example provides a carbon-coated aluminum foil, which is different from Example 1 in that the carbon layer of the carbon-coated aluminum foil does not contain carboxymethyl cellulose hydrogel. Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0056] Test Case 1. Participants In this test example, the carbon-coated aluminum foils prepared in Examples 1 to 13 and Comparative Example 1 were used as test objects to conduct relevant performance tests.

[0057] 2. Test content Tensile strength refers to the stress at which a material produces maximum uniform plastic deformation. In a tensile test, the maximum tensile stress to which a specimen is subjected until it breaks is the tensile strength. The tensile strength is calculated using the following formula: σt = p / (b×d), where σt is the tensile strength (MPa); p is the maximum load (N); b is the specimen width (mm); and d is the specimen thickness (mm).

[0058] Elongation (δ) is an indicator that describes the plastic properties of a material - elongation δ and cross-sectional shrinkage ψ. The elongation is the percentage of the total deformation ΔL of the gauge section after the specimen is tensile fractured to the original gauge length L: δ = ΔL / L × 100%.

[0059] The elongation and tensile strength of carbon-coated foil are obtained by universal tensile testing. The specific test steps are as follows: (1) Sample preparation Prepare carbon coated foil as test samples, ensure that its size, shape and surface treatment meet the test requirements, and mark and number the test samples for subsequent testing and recording.

[0060] (2) Universal tensile machine settings Turn on the universal tensile testing machine, set the test mode to tensile testing, and select appropriate fixtures and test speed. This experiment was set to 50 mm / min.

[0061] (3) Sample clamping Clamp the test specimen into the fixture of the universal tensile machine, making sure it is clamped securely.

[0062] (4) Testing Start the universal tensile testing machine and begin the test. The universal tensile testing machine will apply load to the test sample and record the loading force and the corresponding extension.

[0063] In addition, the electrical properties of the carbon-coated aluminum foil are also tested. Specifically, the carbon-coated aluminum foil is used in the preparation of lithium batteries, and the lithium battery cycle performance is tested to characterize the electrical properties of the carbon-coated foil. The specific steps are as follows: A. Preparation of lithium batteries ① Preparation of positive electrode: Using LiCoO 2 Using carbon black as a positive electrode active material and a conductive agent, a positive electrode active material layer is formed on the surface of a positive electrode current collector (i.e., the carbon-coated aluminum foil prepared in Examples 1 to 13 and Comparative Example 1), thereby preparing a positive electrode sheet; ② Preparation of negative electrode sheet: copper foil is used as negative electrode current collector, silicon-based material is used as negative electrode active material, carbon black is used as conductive agent, and a negative electrode active material layer is formed on the surface of the negative electrode current collector to prepare a negative electrode sheet; ③ Selection of diaphragm: Alumina ceramic-coated polyethylene diaphragm is used as the diaphragm for assembling lithium batteries; ④ Preparation of electrolyte: Propylene carbonate, ethylene carbonate and ethyl methyl carbonate are mixed in a mass ratio of 1:1:1 to obtain a carbonate solvent, and LiPF is added to the carbonate solvent. 6 , prepared to contain 1 mol·L -1 LiPF 6 A carbonate solution, using the carbonate solution as an electrolyte for a lithium battery; ⑤ Assembly of lithium battery: stack the positive electrode sheet, isolation film and negative electrode sheet prepared above in order to prepare a bare cell, then place the bare cell in the outer packaging shell of the lithium battery, inject electrolyte after drying, and obtain a lithium battery through vacuum packaging, standing, formation, shaping and other processes.

[0064] B. Lithium battery cycle performance test Step 1. Initially charge the lithium battery; Step 2. Discharge the lithium battery; Step 3. Repeat steps 1 and 2, record the initial discharge capacity of the lithium battery and the discharge capacity during each cycle of charge and discharge, and cycle the lithium battery until the cycle capacity retention rate of the lithium battery is below 80%, and record the number of cycles of the lithium battery at this time, where: Cycle capacity retention rate of the nth cycle (%) = discharge capacity of the nth cycle / initial discharge capacity × 100%; In the above charge and discharge cycle, the relevant experimental operation parameters and environmental parameters are as follows: charge / discharge current, 0.5C / 0.5C; charge / discharge voltage, 3.0V / 2.0V; temperature, 25°C; humidity, 60%.

[0065] 3. Experimental results Table 1 Test results of relevant properties of carbon-coated aluminum foil

[0066] The relevant performance test results of the carbon-coated aluminum foils prepared in Examples 1 to 13 and Comparative Example 1 are shown in Table 1.

[0067] Compared with Comparative Example 1, in the preparation process of the carbon-coated foil in Examples 1 to 13, a self-healing hydrogel is introduced into the carbon layer. The test results show that the toughness of the carbon-coated foil provided by Examples 1 to 13 is higher than that of the comparative example, which is specifically reflected in the lower elongation and the higher tensile strength than that of Comparative Example 1. This is mainly because the carbon-coated foil provided by Examples 1 to 13 introduces a self-healing hydrogel into the carbon layer arranged on the surface of the foil. Since the self-healing hydrogel contains a large number of non-covalent bonds or covalent bonds, when the carbon-coated foil is subjected to external stimuli, the self-healing hydrogel can be re-cross-linked through the reversible reaction of the non-covalent bonds or covalent bonds therein to complete the self-repair process, thereby achieving self-healing. Therefore, when the carbon-coated foil is damaged under stress stretching, the self-healing hydrogel in the carbon layer undergoes a reversible reaction and re-cross-links through the above-mentioned non-covalent bonds or covalent bonds to repair the damaged part of the foil at the microscopic level. The toughness of the carbon-coated aluminum foil is improved through the above-mentioned action, and the carbon-coated foil is given a lower elongation and a higher tensile strength.

[0068] By comparing the elongation and tensile strength test results of the carbon-coated foils of Examples 1 to 5, it can be seen that the carbon layer in the carbon-coated foil provided in Example 1 contains carboxymethyl cellulose hydrogel, and the carbon layers in the carbon-coated foils provided in Examples 2, 3, 4, and 5 contain cellulose ether hydrogel, nanocellulose hydrogel, carboxymethyl xylan hydrogel, and carboxymethyl guar gum hydrogel, respectively. The test results show that the elongation of the carbon-coated foils prepared in Examples 2 to 5 is higher than that in Example 1, while the tensile strength is lower than that in Example 1, which indicates that compared with other types of hydrogels, the use of cellulose-based hydrogels in the carbon layer of the carbon-coated foil can make the carbon-coated foil have good toughness and a lower risk of fracture; while the elongation of the carbon-coated foil prepared in Example 1 is lower than that in Examples 2 to 3, and the tensile strength is higher than that in Examples 2 to 3, which indicates that compared with other types of cellulose-based hydrogels, the use of sodium carboxymethyl cellulose hydrogel in the carbon layer of the carbon-coated foil can further improve the toughness of the carbon-coated foil, so that the carbon-coated foil has more excellent mechanical properties.

[0069] Compared with Example 1, the shell materials of the microcapsules contained in the sodium carboxymethyl cellulose hydrogel in the carbon layer of the carbon-coated foil provided in Examples 6 and 7 are polyvinyl alcohol and chitosan, respectively. The test results show that the elongation of the carbon-coated foil prepared in Example 1 is lower than that of Examples 6~7, and the tensile strength is higher than that of Examples 6~7. This shows that although polyvinyl alcohol and chitosan can both be used as shell materials for microcapsules, when the hydrogel containing them as the microcapsule shell is applied to the carbon layer of the carbon-coated foil, its toughness and mechanical properties are worse than those of the carbon-coated foil using the hydrogel containing glucose as the microcapsule shell through hydrothermal reaction cross-linking.

[0070] Compared with Example 1, the repair materials of the microcapsules contained in the sodium carboxymethyl cellulose hydrogel in the carbon layer of the carbon-coated foil provided in Examples 8 and 9 are methyl dimethacrylate and colloidal gold, respectively. The test results show that the elongation of the carbon-coated foils prepared in Examples 8 to 9 is higher than that in Example 1, while the tensile strength is lower than that in Example 1.

[0071] Compared with Example 1, the sodium carboxymethyl cellulose hydrogel in the carbon layer of the carbon-coated foil provided in Example 10 does not contain microcapsules. Test results show that the elongation of the carbon-coated foil prepared in Example 10 is higher than that in Example 1, while the tensile strength is lower than that in Example 1.

[0072] Compared with Example 1, the contents of sodium carboxymethyl cellulose hydrogel in the carbon layer of the carbon-coated foil provided in Examples 11 to 13 are 0.06%, 3%, and 15.79%, respectively. The test results show that the elongation of the carbon-coated foil provided in Example 11 is higher than that in Example 1, and the tensile strength is lower than that in Example 1. This is mainly because the content of hydrogel in the carbon layer of the carbon-coated foil in Example 11 is too low, which makes the toughness and mechanical properties of the carbon-coated foil worse than those in Example 1; the elongation of the carbon-coated foil provided in Example 12 is slightly higher than that in Example 1, and the tensile strength is slightly lower than that in Example 1. The elongation and tensile strength of the carbon-coated foil in Example 13 are both equivalent to those in Example 1, which indicates that with the increase of the hydrogel content in the carbon layer of the carbon-coated foil, the toughness and mechanical properties of the carbon-coated foil are increased, and the toughness will gradually tend to be stable, but the electrical properties of the carbon-coated foil will decrease.

[0073] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A carbon-coated foil, characterized in that: The carbon-coated foil comprises a foil and a carbon layer disposed on at least one surface of the foil, the carbon layer comprising a self-healing hydrogel, and the self-healing hydrogel comprises a cellulose-based hydrogel; The cellulose-based hydrogel comprises microcapsules, wherein the microcapsules comprise a repair material and a shell covering the repair material, wherein the repair material comprises a cellulose derivative and cellulase, and the shell is formed by cross-linking glucose.

2. The carbon-coated foil according to claim 1, characterized in that: The cellulose-based hydrogel includes at least one of sodium carboxymethylcellulose hydrogel, sodium hydroxyethylcellulose hydrogel, sodium hydroxypropylmethylcellulose hydrogel, cellulose ether hydrogel, and nanocellulose hydrogel.

3. The carbon-coated foil according to claim 1, characterized in that: The cellulose-based hydrogel is prepared by the following steps: S1. mixing the first solvent with glucose to obtain a glucose solution; S2. mixing hydrogen peroxide with a cellulose derivative to prepare a suspension; S3. Add the repair material to the suspension and mix well to obtain a first mixed solution; S4. mixing the glucose solution with the first mixed solution to obtain a second mixed solution; S5. Allow the second mixed solution to undergo a hydrothermal reaction to obtain a cellulose-based hydrogel, wherein the temperature of the hydrothermal reaction is 110-130°C.

4. The carbon-coated foil according to claim 1, characterized in that: The mass fraction of the self-healing hydrogel in the carbon layer is 0.1-10%.

5. A pole piece, characterized in that: The pole piece comprises the carbon-coated foil as claimed in any one of claims 1 to 4.

6. A battery, characterized in that: The battery comprises the electrode piece as claimed in claim 5.